2011
DOI: 10.1111/j.1525-1470.2011.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the IRF6 gene associated with facial asymmetry in a family affected with Van der Woude Syndrome

Abstract: This report describes a novel missense mutation in the interferon regulation factor 6 (IRF6) gene associated to facial asymmetry. This new feature widens the phenotype spectrum of Van der Woude syndrome (VWS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Since discovery of IRF6 , case reports and case series from a wide geographical distribution have expanded the phenotypic spectrum of VWS (Kayano et al, ; Kim et al, ; Shotelersuk et al, ; Wang et al, ; Gatta et al, ; Ghassibe et al, ; Matsuzawa et al, ; Item et al, ; Ye et al, ; Du et al, ; Brosch et al, ; Paranaiba et al, ; Tan et al, ; de Lima et al, ; Yeetong et al, ; Malik et al, ; Scioletti et al, ; Birkeland et al, ; Minones‐Suarez et al, ; Salahshourifar et al, ). While most studies of VWS have identified point mutations in IRF6 , deletions as large as 2.98 Mb, involving 25 genes, have also been reported (Sander et al, ; Schutte et al, ; Salahshourifar et al, ).…”
Section: Mutations In Irf6 Cause Vws and Ppsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since discovery of IRF6 , case reports and case series from a wide geographical distribution have expanded the phenotypic spectrum of VWS (Kayano et al, ; Kim et al, ; Shotelersuk et al, ; Wang et al, ; Gatta et al, ; Ghassibe et al, ; Matsuzawa et al, ; Item et al, ; Ye et al, ; Du et al, ; Brosch et al, ; Paranaiba et al, ; Tan et al, ; de Lima et al, ; Yeetong et al, ; Malik et al, ; Scioletti et al, ; Birkeland et al, ; Minones‐Suarez et al, ; Salahshourifar et al, ). While most studies of VWS have identified point mutations in IRF6 , deletions as large as 2.98 Mb, involving 25 genes, have also been reported (Sander et al, ; Schutte et al, ; Salahshourifar et al, ).…”
Section: Mutations In Irf6 Cause Vws and Ppsmentioning
confidence: 99%
“…Both the cartoon and sphere models were created using PyMol. Scioletti et al, 2010;Birkeland et al, 2011;Minones-Suarez et al, 2011;Salahshourifar et al, 2011). While most studies of VWS have identified point mutations in IRF6, deletions as large as 2.98 Mb, involving 25 genes, have also been reported (Sander et al, 1994;Schutte et al, 1999;Salahshourifar et al, 2011).…”
Section: Mutations In Irf6 Cause Vws and Ppsmentioning
confidence: 99%
“…For example, Bartsocas-Papas syndrome is a recessive pterygia syndrome characterized by multiple popliteal pterygia, CL/P, ankyloblepharon, synechia, and syndactyly. This disorder is caused by mutations in Receptor-interacting serine/threonine kinase 4 (RIPK4) (Kalay et al 2012;Mitchell et al 2012). As noted earlier, the cardinal features of EEC are similar to some of the features of VWS.…”
Section: Evidence For Genetic Modifiers In Vws and Ppsmentioning
confidence: 71%
“…Identification of genes causing these syndromes has been very successful ) and has been further facilitated by advances in sequencing technology. Exome sequencing recently identified genes causing Kabuki syndrome (Ng et al 2010a) and Bartsocas-Papas syndrome (Kalay et al 2012;Mitchell et al 2012).…”
Section: Mendelian Forms Of Orofacial Cleftsmentioning
confidence: 99%
See 1 more Smart Citation